Relationally Charged: How and When Workplace Friendship Facilitates Employee Interpersonal Citizenship - Xiao, Jincen; Mao, Jih-Yu; Quan, Jing; Qing, Tao (Frontiers in Psychology, 2020)
Having friends at the workplace not only provides an employee joy and meaning, but also facilitates one’s positive behavior. In this study, we argue that workplace friendship has positive influence on an employee’s interpersonal citizenship behavior. Drawing upon conservation of resources theory, the present study explores how and when workplace friendship fosters interpersonal citizenship. Using a time-lagged, multisource data of 620 employees from 83 workgroups, we found that workplace friendship increases an employee’s relational energy, which subsequently, leads to greater interpersonal citizenship. Moreover, we discovered relational-interdependent self-construal as an important moderating influence that affects the saliency of this relationship. Specifically, for employee with a relational-interdependent self-construal, workplace friendship has a stronger positive influence on one’s relational energy and hence interpersonal citizenship. Contributions to theory and practice are also discussed.